محلات PS - Mohammad Rami Halaweh; Haytham AbdAlqader Saleh (My University, 2022)
First thing that comes in mind to people when we talk about shopping is that they expect to go to different shops to find what they need and even so after going to different shops and spending an enormous amount of time they might not find what they were looking for specifically[1], also taking in mind the unexpected prices for the products which they would spend time also in negotiating, let’s also not forget the shops that they might like but they are unfamiliar with them nor their location. In our application we seek to help people who want to go shopping but also want to avoid all the troubles they face which is considered stressful and to help shop owners that want people to know about them[2], but it might be difficult for them for a variety of reasons which might be location or being a new shop …etc. and let’s not forget that a lot of times shops want to announce offers but a lot of times it might go unnoticed. Our project tends to seek out these sorts of issues and provide a solution for them and considering that it is also a mobile application gives us the benefit that it is available for everyone taking in mind that most of the people nowadays in our society carry a smart phone, and it is a user-friendly application[3].